UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MTS RAUDATUL ULUM KARANGPLOSO - Dendi Kuswanto; Khoirul Asfiyak; Moh Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The reason for this study is to portray the job of Islamic strict training educators inexpanding understudy learning inspiration at MTs Raudhatul Ulum Karangploso,depict the procedures of Islamic strict schooling instructors in further developingunderstudy learning at MTs Raudhatul Ulum Krangploso, depict the repressing andsupporting variables in expanding understudy learning inspiration in MTs RaudatulUlum Karangploso. This examination utilizes a subjective methodology with a kindof contextual investigation approach. In gathering information, this study utilizedperception techniques, meetings and documentation. In the mean time, in actuallytaking a look at the legitimacy of information by testing trust, adaptability,steadfastness and confirmability. The results showed that the role of Islamic religiouseducation teachers in motivating students to improve learning outcomes at MTsRaudhatul Ulum Karangploso, namely Using varied teachi. Methods Islamic religiouseducation teacher strategies in improving student learning outcomes at MTsRaudhatul Ulum Krangploso, namely teachers here must attend training first toimprove the quality and learning resources. Inhibiting factors in motivating studentsThe supporting factor in motivating student learning is that teachers can providerewards in learning so that students learn harder.